2019
DOI: 10.3390/en12203961
|View full text |Cite
|
Sign up to set email alerts
|

Simulation Study of Allied In-Situ Injection and Production for Enhancing Shale Oil Recovery and CO2 Emission Control

Abstract: The global greenhouse effect makes carbon dioxide (CO2) emission reduction an important task for the world, however, CO2 can be used as injected fluid to develop shale oil reservoirs. Conventional water injection and gas injection methods cannot achieve desired development results for shale oil reservoirs. Poor injection capacity exists in water injection development, while the time of gas breakthrough is early and gas channeling is serious for gas injection development. These problems will lead to insufficien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Several CO 2 huff-and-puff field practices at home and abroad, comprehensive analysis results of implementation plans, and development effects of CO 2 huff-and-puff field applications in heavy oil and fault-block reservoirs have indicated that wells in the lower structural position show better performance in CO 2 huff and puff. Moreover, for the fault-block reservoir, the limitation of horizontal well arrangement along the direction of structural rise is identified as three rows [40,41]. We have calculated the development conditions of the CO 2 synergistic huff-and-puff well group, which include the number of synergistic huffand-puff wells, structural position of synergistic wells, positional relationship between the synergistic wells' ligature and structural contour, synergistic well spacing, CO 2 injection volume, and type of well pattern.…”
Section: Research Program 241 Synergistic Modementioning
confidence: 99%
“…Several CO 2 huff-and-puff field practices at home and abroad, comprehensive analysis results of implementation plans, and development effects of CO 2 huff-and-puff field applications in heavy oil and fault-block reservoirs have indicated that wells in the lower structural position show better performance in CO 2 huff and puff. Moreover, for the fault-block reservoir, the limitation of horizontal well arrangement along the direction of structural rise is identified as three rows [40,41]. We have calculated the development conditions of the CO 2 synergistic huff-and-puff well group, which include the number of synergistic huffand-puff wells, structural position of synergistic wells, positional relationship between the synergistic wells' ligature and structural contour, synergistic well spacing, CO 2 injection volume, and type of well pattern.…”
Section: Research Program 241 Synergistic Modementioning
confidence: 99%
“…[16] used the molecular dynamics simulation method to find that supercritical CO 2 can affect shale oil in both inorganic and organic nanopores, but water only works in inorganic nanopores. H. Yu [17] found that CO 2 huff-n-puff could more effectively improve oil recovery for shale with an ultra-low permeability through the numerical simulation method. Gamadi and Li L. et al [18,19] used a component simulator to analyze the effects of reservoir heterogeneity, soaking time, injection pressure, and huff-n-puff cycles on EOR.…”
Section: Introductionmentioning
confidence: 99%